1992
DOI: 10.1016/0378-1097(92)90137-d
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of pag gene expression in Bacillus anthracis: use of a pag-lacZ transcriptional fusion

Abstract: The production of protective antigen (PA), the common component of the two anthrax toxins, is influenced by the environment. In order to examine factors involved in its regulation, a transcriptional fusion between the promoter region of the PA gene (pag) and the lacZ gene was constructed and introduced into Bacillus anthracis Sterne. Activity of the pag promoter was followed by measuring beta-galactosidase activities under various growth and medium conditions. Expression from the pag promoter was observed thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 13 publications
3
21
0
Order By: Relevance
“…As noted previously (40), upstream ofpag there are exact (TATAAT) and nearly exact (TTGAAA versus TTGACA) matches to the -10 and -35 consensus sequences recognized by the primary housekeeping o# of B. subtilis RNA polymerase (27). The implication that pag is transcribed during exponential growth phase is consistent with a prior demonstration that the amount of lethal toxin parallels cell density (8) and with a recent report that expression from the pag promoter occurs throughout the exponential growth phase (4). Another notable feature of the putative pag promoter region is that the -10 and -35 sequences are potentially sequestered within an extended stem-loop structure, nucleotides 1722 to 1779 (40), having a AGf of -15.8 kcal (ca.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As noted previously (40), upstream ofpag there are exact (TATAAT) and nearly exact (TTGAAA versus TTGACA) matches to the -10 and -35 consensus sequences recognized by the primary housekeeping o# of B. subtilis RNA polymerase (27). The implication that pag is transcribed during exponential growth phase is consistent with a prior demonstration that the amount of lethal toxin parallels cell density (8) and with a recent report that expression from the pag promoter occurs throughout the exponential growth phase (4). Another notable feature of the putative pag promoter region is that the -10 and -35 sequences are potentially sequestered within an extended stem-loop structure, nucleotides 1722 to 1779 (40), having a AGf of -15.8 kcal (ca.…”
Section: Discussionsupporting
confidence: 89%
“…Bartkus and Leppla (1) reported that production of PA is transcriptionally regulated by bicarbonate, that a trans-acting factor is required for pag transcription, and that at least some of the genes involved are located on the toxin plasmid pXOl. Evidence for such a factor was also provided by Cataldi et al (4,5). Recently, two classes of B. anthracis insertion mutants altered in toxin production were described (15).…”
mentioning
confidence: 85%
“…In B. anthracis, transcription of the genes encoding the virulence-associated capsule and anthrax tripartite toxin is activated by bicarbonate (Bartkus and Leppla, 1989;Cataldi et a/., 1992;Koehler et a/., 1994;Sirard et a/., 1994;Uchida et a/., 1993a), and bicarbonate-stimulated expression of both toxin and capsule genes is dependent on the trans-acting factors of atxA and acpA, respectively (Dai eta/., 1995;Vietri eta/., 1995). Because synthesis of these virulence factors responds to the same signal, bicarbonate, it seemed likely that there might exist some interaction or cross-talk between the two regulatory systems.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative studies ofpag gene expression using B. anthracis strains harboring transcriptional fusions in trans have been conducted previously (1,3). It has been shown that bicarbonate activates pag expression throughout the exponential growth phase and maximally in the late log phase.…”
mentioning
confidence: 99%